Deterioracja elewacji zewnętrznych wywołana biofilmem = Deterioration of the external façade caused by biofilm - Piontek, Marlena; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The external elevations are destroyed as a result of the presence of microorganisms that make them active layer known as a biofilm. This phenomenon leads to changes in the structure of the material and reduce their value. Privacy exteriors is reducing or eliminating factors that contribute to biological corrosion. The article is a compendium of knowledge about the phenomenon of deterioration elevation caused by biological factors.
Keywords: biofilm; deterioracja; elewacje zewnętrzne; deterioration; external facades